Clinical Placement Experience, Supervision, and Nursing Career Aspirations of Undergraduate Nursing Students in Sarawak, Malaysia - Mohammed Rasheedan, Ellin; Dayang Zuraina, Abang Haji Kashim (ASIAN SCHOLARS NETWORK, 2024)
This study aimed to explore nursing students' perceptions of the clinical learning environment and mentorship during their clinical placement in hospitals and how these factors relate to their intention to work as a nurse upon graduation. A survey was conducted among nursing students who had completed at least 12 months of clinical practice in hospitals located in Kuching, Sarawak, between January 2022 and February 2023. Data were analysed using percentages, frequencies, mean, standard deviation, t-test, Pearson's correlation, ANOVA, and regression analysis. Our findings revealed a significant correlation between the sociodemographic characteristic such as age of students and year of study towards clinical learning experience. Student perceived ward as good learning environment, clinical teacher teaching expertise, and clinical teacher ability to integrate between knowledge and practice rated the most satisfying element in students’ clinical experience. Our study established a significant correlation between student age, year of study, and their clinical learning experiences. Students found the ward environment, clinical teacher expertise, and knowledge-to-practice integration to be highly satisfying elements in their clinical education.